1972
DOI: 10.1530/jrf.0.0310249
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction in the Long-Tongued Bat, Glossophaga Soricina

Abstract: Summary. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The use of these species of bats is especially pertinent because they share some reproductive similarities with primates, both anatomically and with respect to ovulation patterns. For example, Glossophaga soricina are polyoestrous mono-ovulates with menstrual cycles of 22 to 26 days, including a luteal phase and periodic endometrial shedding [ 34 ]. Antonio-Rubio and colleagues [ 33 ] demonstrated that the ovaries of Artibeus jamaicensis , Glossophaga soricine , and Sturnira lilium are polarized, with a medullary region containing developing follicles and a cortical region containing both primordial follicles and a population of cells which looked similar to germ cells histologically.…”
Section: Introductionmentioning
confidence: 99%
“…The use of these species of bats is especially pertinent because they share some reproductive similarities with primates, both anatomically and with respect to ovulation patterns. For example, Glossophaga soricina are polyoestrous mono-ovulates with menstrual cycles of 22 to 26 days, including a luteal phase and periodic endometrial shedding [ 34 ]. Antonio-Rubio and colleagues [ 33 ] demonstrated that the ovaries of Artibeus jamaicensis , Glossophaga soricine , and Sturnira lilium are polarized, with a medullary region containing developing follicles and a cortical region containing both primordial follicles and a population of cells which looked similar to germ cells histologically.…”
Section: Introductionmentioning
confidence: 99%
“…Menstruation occurs shortly after copulation, at or shortly after ovulation, and most endometrial regeneratlon is deferred untll after ovulation. The ovum 1s retalned in the oviduct during thls perlod (Rasweiler, 1972;Quintero and Rasweiler, 1974). See also Hamlett (1 934).…”
Section: Discussionmentioning
confidence: 99%